Características epidemiológicas de pacientes obstétricas que ingresaron a UCI en un hospital nivel III, Iquitos 2022-2023 - Santilan Pinedo, Hugo Christopher (2024)
GENERAL OBJECTIVE: To evaluate the epidemiological characteristics of obstetric patients admitted to the ICU in a Level III Hospital, Iquitos 2022-2023 MATERIALS AND METHODS: The methodology to be used is part of a quantitative, descriptive study that seeks to relate the epidemiological characteristics of obstetric patients and admission to the Intensive Care Unit (ICU), as well as their comorbidities. Considering that between 3 to 4 admissions of obstetric patients to the ICU are recorded per month, of which 5% die. The sample will be made up of all cases of obstetric patients admitted to the ICU. The statistical analysis is based on proportion test analysis with the use of the SPSS v.25 package. CONCLUSIONS: The epidemiological characteristics with emphasis on obstetric pathologies are related to ICU admission.